ISOLATION AND MOLECULAR DIAGNOSIS OF ACINETOBACTER BAUMANNII STRAINS FROM VARIOUS CLINICAL SAMPLES AND THEIR CULTURAL PROPERTIES - Waleed Hadi, Huda; AL Sammak , Essra Ghanim (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: For the optimal and accurate isolation of Acinetobacter baumannii bacteria, which are considered bacteria are increasingly serious health problem in the healthcare community, especially immunosuppressed people and residents' patients' hospital, due to its high resistance to antibiotics. Methods: Accordingly, 300 clinical samples were collected from different hospitals in Mosul city from January to June 2023. They were grown on culture media such as MacConkey and Hichrome Agar for isolation purposes, the number and percentage of all isolated strains for each medium were recorded. Molecular screening was also done by recA  gene and 16S rRNA to confirm the diagnosis. Morphological and physiological characteristics were observed on other different media. Results: the 130/43.3% of A. baumannii were isolated from MacConkey medium and 119/91.5% were isolated on Hichrome medium. However, the isolation rate decreased to 15/11.5% in the case of molecular diagnosis with conservative recA gene. The highest isolation rate was from wound samples at 8.3%, followed by urine and burns at the same rate of 7.5%, then throat swabs at 6.6%, followed by sputum at 1.4%, while the bacteria were not isolated from blood, CSF and medical equipment. The morphological characteristics of the bacteria varied greatly on many media such as Eosin –methylene blue EMB medium, Mueller medium, and Nutrient Agar medium in addition to the previous media. Novelty: This research proves the molecular diagnostic ability of the recA gene in A. baumannii bacteria. While highlighting the isolation of these bacteria at the same time on a selective diagnostic medium and comparing the data of these results with each other.